The Implementation of MQTT Protocol using PT-100 for Monitoring the Vaccine Temperature - Sigit Pramono; Slamet Indriyanto; Wahyu Junianto (Ikatan Ahli Informatika Indonesia (IAII), 2022)
A vaccine has an essential role for humans because it can reduce the effect of organism infection and activate the body's immune. The limitation of temperature when the vaccine is stored becomes one of the influential factors for its quality. Since the recent technique used for checking the temperature is manual, the process of real-time temperature monitoring cannot be done and becomes the main problem in the process of storing vaccines. This research is aimed to develop a system for measuring temperature on a chiller through a temperature sensor and the internet of things automatically. The methods used in the MQTT protocol are published and subscribed. The quality of service (QoS) to measure network capability and PT-100 is the sensor in this research because it has a high accuracy level, linear signal change, and fast response. This sensor can measure glycol liquid with a temperature range of 2-8°C. Data distribution uses an ESP module to connect the data to Antares through the wifi network. The temperature value measurement using PT-100 toward vaccine chiller temperature obtains an accuracy value of 99,32%. This accuracy value shows that the result is compatible with the logger data measurement tool development used with an error result of 0.58%. Delay parameter testing on the quality of service level obtains the average value of 41.91 ms, while the Packet loss parameter obtains the value of 0%.